Positive education in college students: the effects of the “self-knowledge and soul care” workshop on the emotions and character strengths: Educación positiva en estudiantes universitarios: efectos del taller “autoconocimiento y cuidado del alma” sobre las emociones y fortalezas del carácter - Barranca Enríquez, Antonia; Romo González, Tania; López Mora, Gloria; Contreras Miranda, Maria de Jesús; Sánchez Silva, Diana María; Hernández Pozo, María del Rocío (Archivos de Medicina (Manizales), 2021)
Objective: most healthy and unhealthy behaviors are acquired or consolidated during youth, thus a good investment in the future of any nation, should be to promote the development of young people, incorporating them into projects and programs that aspire to increase their subjective wellbeing and personal health. The Psycho-Educational Intervention (PEI) presented here has been shown to have effects on the health andwellbeing of students as well as on their academic performance. However, its effectson strength of character, emotional balance and emotional intelligence are unknown.Materials and methods: in this paper it was shows the effects of this PEI on positiveeducation in a group of 18 students through three questionnaires: VIA-240, PANAS-20and PIEMO. To estimate the effects of the PEI, a comparison was made betweenthe scores obtained on the three questionnaires before and after the PEI sessions.Results: the results show that not only did character strengths, positive affect and emotional intelligence improve with PEI, but that also the character strengths and theemotional bearings arranged in a network topography changed with intervention. Also, there were some changes in the most connected nodes of the network. Conclusions:these results show that PEI improved the previous reported variables, they also show the way in which the balance of the positive and negative affects, the development of emotional intelligence and the enhancement of character strengths give access to the three pillars of positive psychology.